Rétrograde venous perfusion (RVP) for intraçtable venous leg ulcers: a retrospective analysis - Alaa Sharabi; Mohammed Abd-Eltawab; Sherif A. Sharabi; Mai A. Elkalla; Yossef N. Abdelbaky; Mohamed A. Abou Yossef; Ahmed Mousa (European Journal of Medical Research)
Abstract Background Retrograde venous perfusion (RVP) is a minimally invasive procedure in which the limb circulation is isolated by the application of a proximal limb tourniquet, followed by the administration of specific medications through a distal limb vein. This allows these drugs to pass in the reverse direction to reach the ulcerated area of the affected limb. The aim of this study was to evaluate the safety, feasibility, and efficacy of RVP, for the management of long-standing intractable chronic venous leg ulcers (CVLUs). Methods A 4-year retrospective study took place from January 2021 to January 2025. All patients who underwent the RVP technique were included in the study. These patients had chronic, intractable, long-standing, nonhealing, venous leg ulcers. They were classified into two groups. Group I included those who underwent RVP (treated group). However, group II was treated with standard compression therapy (control group). A paired-samples t test was performed to compare the studied groups. Kaplan–Meier survival analysis was performed for patients who were free from ulcer recurrence or nonhealing after the RVP technique. Results During the 4-year study period, 384 patients were retrospectively analyzed. A total of 75% (n = 288) of the participants were females, and 25% were males (n = 96). The median age was 37.26 ± 4.2 years. Ulcers ranged between 30cm2 and near circumferential. The median ulcer duration was 18 ± 14.4 months. The mean number of RVP sessions was 26.78 ± 7.6, whereas the mean session time was 213 ± 49 min. A reduction in ulcer size/complete healing was achieved in 96.9% of the patients in group I vs. 68.8% of those in group II. Conclusions Compared with the standard compression technique, RVP therapy may be considered an effective and feasible technique for treating intractable venous leg ulcers. It offers shorter periods of therapy with a high success rate in reducing ulcer size/complete wound healing within a short period of time. This therapeutic option may provide essential evidence to reduce the negative social and economic impact on affected populations.